AN INSTRUCTIONAL FRAMEWORK FOR INTEGRATING CRITICAL THINKING STRATEGIES IN EFL READING CONTEXTS - Dwi Putri Hartiningsari; Astried Damayanti; Hanif Ika Hastanti (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
This study explores the implementation of an instructional framework for integrating critical thinking strategies in English as a Foreign Language (EFL) reading contexts. Employing a qualitative case study design, the research was conducted in a Reading for General Communication course involving one lecturer and first-semester students. Data were collected through semi-structured interviews, classroom observations, and students’ reflective writings and were analyzed using thematic analysis to identify patterns in instructional practices and student engagement. The findings comprise three stages: activation, exploration, and reflection. The activation stage engages students by connecting prior knowledge with new reading materials through guided discussions, lecturer facilitation, and authentic learning resources. The exploration stage promotes higher-order thinking through problem-based tasks, collaborative learning activities, and structured argumentation that encourage students to analyze, evaluate, and justify ideas. The reflection stage fosters metacognitive awareness by providing opportunities for independent learning, self-assessment, and reflective activities that help students monitor their comprehension and reasoning processes. The integration supports the development of critical thinking. The framework enhances students’ analytical, evaluative, logical reasoning, and problem-solving abilities while encouraging active engagement with texts. These findings offer practical insights for EFL educators seeking to systematically integrate critical thinking strategies into reading instruction.